1994
DOI: 10.1108/09600039410055972
|View full text |Cite
|
Sign up to set email alerts
|

Computerization: Supporting Integration

Abstract: Fast and flexible low-cost data processing and information systems have transformed business operations. Through enhanced information availability, leading manufacturers have accelerated the flow of their products to create competitive advantage based on speed. These companies have developed methods to channel the power of information in order to use organizational resources more effectively and facilitate the management of activities both within and outside the company [1,2]. Internally, interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Many authors claim that Supply Chain Management and information sharing can substantially involve better supply chain performance (Shapiro, 1984;Scott & Westbrook, 1991;Byrne & Javad, 1992;Cooper, 1993;Ellram & Cooper, 1993;Gustin, Stank & Daugherty, 1994;The Global Research Team at Michigan State University, 1995;Christopher, 1998;and Christiansee & Kumar, 2000). But few empirical studies have been conducted to demonstrate this (Vargas, Cardenas &Mattarranz, 2000, andStank, Keller &Daugherty, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors claim that Supply Chain Management and information sharing can substantially involve better supply chain performance (Shapiro, 1984;Scott & Westbrook, 1991;Byrne & Javad, 1992;Cooper, 1993;Ellram & Cooper, 1993;Gustin, Stank & Daugherty, 1994;The Global Research Team at Michigan State University, 1995;Christopher, 1998;and Christiansee & Kumar, 2000). But few empirical studies have been conducted to demonstrate this (Vargas, Cardenas &Mattarranz, 2000, andStank, Keller &Daugherty, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are other empirical studies that analyse the separated effect of internal or external integration programs on performance. The studies considering only the internal integration-performance relationship are Daugherty, Ellinger & Gustin, 1998;Keller, 2000 andStank, Daugherty &. And, the studies analysing only the external integration-performance relationship are: Daugherty, Sabath & Rogers, 1992;Larson, 1994;Daugherty, Ellinger & Rogers, 1995;Groves & Valsamakis, 1998;Stank, Crum & Arango, 1999;Stank, Daugherty & Autry, 1999;Ellinger, Taylor &Scannell, Vickery &Dröge, 2000. We plan to contribute to the existing empirical research on the relationship between SCM and performance by:…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that integration can help firms develop logistics competency. Gustin, Stank, and Daugherty (1994) found that integrated firms are more likely to computerize their business processes, thus achieving significant tangible results including substantial inventory savings and lead time reductions. Process integration also ensures that operational interfaces within firms are synchronized to reduce duplication, redundancy, and dwell time (Rodrigues, Stank, and Lynch 2004).…”
Section: Internal Process Integration and Logistics Service Competencymentioning
confidence: 99%
“…One popular notion as suggested by the following stream of research argues that IT supports logistical integration through the free flow of critical information, and thus increases operational efficiency and customer responsiveness (Tan, 1999). For instance, by integrating logistics firms into clusters and implementing the integrated logistics concept, Gustin et al (1994;1995) show that these clusters have significantly higher computerisation of various logistical information, and higher levels of information availability (from both within logistics and other functional areas) than non-integrated firms.…”
Section: Introductionmentioning
confidence: 98%